Knowledge and Awareness of Rural People About Currently Emerging Disease Bird Flu - Alam, M Jahangir; Ali, K Mohammad; Selimuzzaman, ABM (TAJ: Journal of Teachers Association, 2010)
A descriptive type of cross-sectional study was conducted in a village Gohordo of Gabtoli Upazila, Bogra to assess the knowledge and awareness of people of age above 18 years and above about "bird flu", its modes of transmission and prevention, by an interviewer administered questionnaire. The questionnaire was pretested and data were collected using purposive sampling technique. In this study it was found that out of 418 people, 231(55.26%) were female and the rest 187 (44.74%) were male. Majority of the respondents 226 (54.06%) were in the age group of 20-40 years, followed by 29.19%, 8.85% and7.89% were in the age groups of 40-60,<20 and above>60 years respectively. More than half; 226 (54.06%) of the people heard the term ‘bird flu'; majority of them (95.13%) as a disease. Among 226, 193(85.39) respondents know that the disease may transmit to human population. But only 32, (30%) people think that this disease is transmitted by keeping infected birds & suspected poultry, followed by 19.02% who think that it transmitted by caring & culling poultry. Among the people who heard the name of the disease,95 (42%) people had no knowledge about the signs and symptoms of the disease and only 20.35% respondents knew poultry carrying people and poultry meat eaters as "susceptible groups" getting infection. About 195 (77.43%) people know that this disease is preventable. About 55.31% and 37.16% people think, partially cooked meat and half boiled egg respectively may spread the disease to man. There is a strong association of literacy with the knowledge of the disease (p<0.05). This study will emphasize the proper health education to create awareness of the people for prevention of bird flue. DOI: 10.3329/taj.v22i1.5019 TAJ 2009; 22(1): 54-58